SINERGI MAQASHID AL-SYARIAH, KONSTITUSI, DAN MASYARAKAT SIPIL DALAM MENANGKAL RADIKALISME DAN EKSTREMISME BERAGAMA - Kausar, Ira; Mustar, Mustar; Sukti, Surya (MAQASHID, 2025)
Abstract: Acts of radicalism and religious extremism are often associated with religious teachings that are considered deviant from what they should be because they lead to acts of terrorism. Radicalism is ideological thinking with the aim of achieving change through more systematic or organized methods. Meanwhile, religious extremism is thinking or behavior that is very radical and often leads to acts of violence and intolerance to differences. This research is a literature study that examines efforts to resolve radicalism and religious extremism through the constitution, civil society and law in Indonesia. The results of the discussion explain: in the Radicalism section, the government emphasizes the importance of Pancasila and the Law as the basis of life so as not to deviate and be radical about the order of the Indonesian state. While in the Religious Extremism section which leads to acts of terrorism, the government issued regulations PP No. 77 of 2019 concerning the Prevention of Criminal Acts of Terrorism and Law No. 5 of 2018 concerning Eradication of Criminal Acts of Terrorism, besides that prevention is carried out through religious-based educational institutions and community efforts through social media and community organizations. The value of legal philosophy shown is through a deep understanding of radicalism and religious extremism in Indonesia which is extracted from religious, social and political values. Keywords: Radicalism, Religious Extremism, Prevention.